The relationship between emotional intelligence & injury in wrestlers - Kalkhoran, J. F.; Ghelichpoor Dashlibroon, B.; Shariati, A. (International Journal of Kinesiology & Sports Science, 2013)
In this study, emotional intelligence, which is the ability to understand the excitement and emotion, was evaluated in Iranian elite wrestlers (with the mean age 19.40±5.5years) to determine its relationship with sports injuries. For this purpose, 90 wrestlers, who had participated in Country Championships and who had been invited to Iranian national team in 2012, participated in this research. For data collection, profile sheets, the Schulte Self Report Emotional Intelligence Test, sports injury reports and interviews with athletes and team physicians in addition to available medical records were used. Based on the wrestlers` injury reports, there was an average of 12 injuries in 2012. The results showed significant negative relationships between the ability of wrestlers to regulate emotions (p=-0.309), their ability to use emotions (p=-0.313), their ability to assess their emotions (p=-0.582), their ability to generally regulate their emotions (p=-0.445) with the number of sports injuries. Also, only the ability to assess the emotions could predict the probability of injuries in wrestlers, that is, the wrestlers who had high ability to regulate their emotions suffered from lower injuries. The significant relationship between the components of emotional intelligence and the number of sports injuries showed that the athletes who had lower ability to regulate their emotional intelligence might put themselves more in risky situations and consequently more injuries. Coaches and officials are recommended to identify these athletes and to improve their emotional intelligence to reduce the probability of their sports injuries.